Risk of Infection and Types of Infection Among Elderly Patients With Inflammatory Bowel Disease: A Retrospective Database Analysis. Issue 3 (13th April 2019) - Khan, Nabeel; Vallarino, Carlos; Lissoos, Trevor; Darr, Umar; Luo, Michelle
Abstract: Background: Inflammatory bowel disease (IBD) treatment in the elderly is challenging in part because of increased risk of infections. The aim of our study was to determine the absolute and relative risk of infections among the elderly IBD patient population and to identify factors affecting the risk of infections in the overall IBD patient population. Methods: A retrospective study of patients with IBD initiating corticosteroids, immunomodulators (IM), or biologic therapy (January 2010–December 2014) was conducted using the Truven Market Scan database. IM and biologic exposure were assessed in a time-dependent manner. ICD-9 codes identified infection during follow-up. A Cox proportional hazards model was fitted to gauge the association between age, other covariates, and infection risk. Results: We identified 63, 759 patients with IBD. We found 2664 infections (incidence rate [IR] = 16.95/100 person-years) among 8788 elderly patients with IBD and 10, 515 (IR = 10.49/100 person-years) among the nonelderly group. Pneumonia (39.8%), sepsis (13.2%), and candidiasis (12.9%) were the most common infections in the elderly. Factors associated with a higher risk of infection included being elderly (HR: 1.27, P < 0.0001), anti-TNF therapy (HR: 1.64, P < 0.0001), IM therapy (HR: 1.32, P < 0.0001), and polypharmacy (HR: 1.32, P < 0.0001). Conclusions: Advanced age, anti-TNF (biologic) therapy, and IM therapy were associated with an increased risk of infection. Pneumonia was the most common infection among the elderly IBD population. Physicians should be mindful of these risks when prescribing medications for elderly patients with IBD, and ensure their patients are adequately vaccinated. Abstract : Advanced age is an independent risk factor for acquiring infections among patients with IBD. Among the elderly IBD patient's polypharmacy, certain comorbidities, anti-TNF therapy, and immunomodulator therapy further increase the risk of infection. Pneumonia is the most common infection among this group.